Effect of CTSS non-synonymous mutations on litter size in Qianbei Ma goats - Zhang, Yuan; Chen, Xiang; Ruan, Yong; Guo, Wei; Chen, Jiajing; Tang, Wen; Ji, Quan; Fu, Kaibin (Frontiers in Veterinary Science, 2023)
Cathepsin S (CTSS) is a member of the cysteine protease family closely related to reproductive regulation in goats. However, its effect on litter size in goats remains unclear. In this study, the relationship between CTSS gene polymorphisms and litter size was revealed by analyzing the DNA sequence and mRNA expression of CTSS in the gonadal axis of Qianbei Ma goats. In addition, bioinformatics methods were used to evaluate the effect of nonsynonymous mutations on CTSS protein structure and function. CTSS was expressed in all parts of the gonadal axis of Qianbei Ma goats, with the highest expression in the uterus in the multi-lamb group and in the fallopian tube in the single-lamb group. The sequencing results showed that four SNPs in CTSS, including g.7413C → T, g.8816A → T, g.9191 T→G and g.10193G → A, were significantly correlated with litter size (P < 0.05). All four analyzed mutation sites were in strong linkage disequilibrium (r 2 > 0.33, D' > 0.70). Additionally, the haplotype Hap1/2 had a significantly higher frequency than the other haplotypes (P < 0.05). g.7413C → T and g.8816A → T were nonsynonymous mutations. The g.7413C → T mutation resulted in the substitution of serine 161 of the CTSS protein with phenylalanine (p.S161F), and the g.8816A → T mutation resulted in the substitution of aspartate 219 with tyrosine (p.N219Y). p.S161F was highly conserved across 13 species and that p.N219Y was relatively conserved in cloven-hoofed species. Mutations at two sites changed the local conformation of the CTSS protein, reduced its stability, and affected its function and goat breed evolution. These findings confirm that CTSS affects the lambing traits of goats and provide a theoretical basis for the regulatory mechanism of CTSS in affecting litter size.